Effects of epigallocatechin-3-gallate (EGCG) on cell cycle distribution and DNA integrity of K562 cells, a human chronic myeloid leukemia - Elda Surhaida Latif,; Siti Nurfarhanah Zahari,; Asmah Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Epigallocatechin-3-gallate (EGCG) is a naturally derived compound from green tea with high antioxidant activity and various anti-cancer properties. EGCG has been widely investigated worldwide. However, effects of EGCG on cell cycle of K562 have not been clearly stated elsewhere. This study was conducted with the aim to investigate the antiproliferative effect of EGCG on K562 human leukemic cells and its underlying mechanism of action on the cells. MTT assay was conducted to determine cytotoxicity effect of EGCG on the K562 cells. Meanwhile, cell cycle analysis and DNA damage on the cells were determined by Flow cytometry and Comet assay respectively. K562 cells were treated with EGCG at concentrations ranging from 0 to 100μg/ml for 48 hours. The results showed that EGCG effectively decreased the percentage of cell viability in a dose dependent manner. The IC10, IC25 and IC50 of EGCG on K562 cell lines were 5 ± 2.44 μg/mL, 10 ± 5.93 μg/mL and 50 ± 1.93 μg/mL, respectively. In cell cycle assay, EGCG has shown no significant effect (p>0.05) on the cell cycle of K562 cell line as compared to negative control, whereas Imatinib mesylate as the positive control showed cell cycle arrest at S phase in this cell line. Hence, EGCG can be verified as a non-cell cycle specific compound. In addition, EGCG was found to cause a significant increase (p<0.05) in tail moment value and percentage of DNA tail in K562 cell line, suggesting DNA damage as an early signal of EGCG induced cell cytotoxicity. In conclusion, by decreasing the cell viability and inducing DNA damage, EGCG showed promising potential as an alternative treatment for leukemia through non-cell cycle specific pathway and further investigation on other mechanisms of action of EGCG on the cells is recommended.